Relasi Islam dan Masyarakat Etnis Tionghoa (Studi Kasus : Komunitas Cina Benteng di Tangerang) - Bambang Permadi (Al Aqidah (Jurnal Studi Islam), 2019)
The purpose of this study was to look at the relationship between Islam and the Chinese ethnic community in the Chinese community fort in Tangerang. This research is a descriptive qualitative study. The results of this study are that Islam can be accepted in all levels of society, including the people in the China Benteng community in Tangerang. The Benteng Chinese accept Islam as a culture and tradition but as a religion that teaches doctrine they do not want to follow it, as religious teachings they prefer other religions that allow their ancestral traditions and they argue that all religions teach goodness together. Buddhism is the religion which is the most chosen by the Chinese Benteng community, while the choice to convert to Islam is the next. Usually the motivation is the closeness of personal relationships with spiritual teachers. The most motivation is marriage with indigenous women.